Atomic resolution mechanistic studies of ribocil: A highly selective unnatural ligand mimic of the E. coli FMN riboswitch. Issue 10 (2nd October 2016) - Howe, John A.; Xiao, Li; Fischmann, Thierry O.; Wang, Hao; Tang, Haifeng; Villafania, Artjohn; Zhang, Rumin; Barbieri, Christopher M.; Roemer, Terry
ABSTRACT: Bacterial riboswitches are non-coding RNA structural elements that direct gene expression in numerous metabolic pathways. The key regulatory roles of riboswitches, and the urgent need for new classes of antibiotics to treat multi-drug resistant bacteria, has led to efforts to develop small-molecules that mimic natural riboswitch ligands to inhibit metabolic pathways and bacterial growth. Recently, we reported the results of a phenotypic screen targeting the riboflavin biosynthesis pathway in the Gram-negative bacteria Escherichia coli that led to the identification of ribocil, a small molecule inhibitor of the flavin mononucleotide (FMN) riboswitch controlling expression of this biosynthetic pathway. Although ribocil is structurally distinct from FMN, ribocil functions as a potent and highly selective synthetic mimic of the natural ligand to repress riboswitch-mediated ribB gene expression and inhibit bacterial growth both in vitro and in vivo . Herein, we expand our analysis of ribocil; including mode of binding in the FMN binding pocket of the riboswitch, mechanisms of resistance and structure-activity relationship guided efforts to generate more potent analogs.